World Bank Group Activities in Situations of Conflict and Violence : An IEG Evaluation - Independent Evaluation Group (World Bank Group, Washington, DC, 2014)
Fragility, conflict, and violence are at the heart of the World Bank Group strategy to attain the twin goals of ending poverty and promoting shared prosperity. Establishment of fragility, conflict, and violence (FCV) as one of the cross-cutting solution areas under the Global Practice Vice Presidency reflects the high level of priority attached to this theme. The FCV cross-cutting solution area is expected to enhance a systematic and coordinated approach across the Bank Group. The Independent Evaluation Group (IEG) of the World Bank Group contributed to this effort by undertaking an evaluation, World Bank Group Assistance to Low-Income Fragile and Conflict-Affected States: an Independent Evaluation (IEG 2014). This report focused on assessing Bank Group activities in low income countries classified as fragile and conflict-affected. Recognizing the significant implications of conflict and violence to the attainment of the Bank Group s strategic goals the CODE agreed that the follow-up evaluation would capture the different nature of fragility and manifestations of violence in countries not on the World Bank Group list of fragile and conflict-affected situations. The CODE noted that such forms of fragility and violence could include IBRD and blend countries, small island states, fragility due to organized crime and violence, and fragility due to ethnic tensions. The proposed evaluation is intended to respond to this demand and to broaden the Bank Group s perspectives on addressing the development challenges arising from conflict and violence.